Retorika tabligh (Teknik berpidato) - zulhasan latif (Universitas Islam Negeri Imam Bonjol Padang, 2004)
In doing the dakwah activity, we need to used communication strategy or communication planning to reach the goal. Communication strategy should. be arrange sistematically, flexible, appropriate elements of dakwah. To get the effectiveness of dakwah, we should use effective communication that must be processed through 'two ways communication